New Horizons in Therapeutic Antibody Discovery: Opportunities and Challenges versus Small-Molecule Therapeutics. (April 2015) - Smith, Alison J.
Antibody drugs have become an increasingly significant component of the therapeutic landscape. Their success has been driven by some of their unique properties, in particular their very high specificity and selectivity, in contrast to the off-target liabilities of small molecules (SMs). Antibodies can bring additional functionality to the table with their ability to interact with the immune system, and this can be further manipulated with advances in antibody engineering. This review summarizes what antibody therapeutics have achieved to date and what opportunities and challenges lie ahead. The target landscape for large molecules (LMs) versus SMs and some of the challenges for antibody drug development are discussed. Effective penetration of membrane barriers and intracellular targeting is one challenge, particularly across the highly resistant blood-brain barrier. The expanding pipeline of antibody-drug conjugates offers the potential to combine SM and LM modalities in a variety of creative ways, and antibodies also offer exciting potential to build bi- and multispecific molecules. The ability to pursue more challenging targets can also be further exploited but highlights the need for earlier screening in functional cell-based assays. I discuss how this might be addressed given the practical constraints imposed by high-throughput screening sample type and process differences in antibody primary screening.